A novel variable antibody fragment dimerized by the dHLX peptide with enhanced affinity against amantadine compared to its corresponding scFv antibody. Issue 1 (1st January 2018) - Xie, Sanlei; Wen, Kai; Peng, Tao; Wang, Jianyi; Yao, Kai; Jiang, Haiyang
ABSTRACT: Amantadine (AMA) is an illegally used antiviral drug in the poultry industry, it is necessary to establish a fast, accurate and time-saving detection method for poultry food. The antibody-based immunoassay can achieve fast and accurate requirements. We developed a recombinant antibody-based specificity immunoassay for AMA. In the recombinant antibody, the heavy chain variable region (VH) is connected covalently with the light chain variable region (VL) by the artificial linker. Here, two recombinant antibodies' single-chain variable fragment (scFv) and scFv-dHLX were constructed and functionally expressed in the periplasm of Escherichia coli . The helix-turn-helix peptide was utilized to dimerize VH and VL similar to the IgG counterpart. The ScFv-dHLX protein showed a higher binding ability and affinity resulting in improvement of in vitro affinity activity over its corresponding scFv. Our results not only indicated scFv-dHLX as an alternative for scFv in analytical application, but also offered a novel and efficient hetero-dimerization pattern of VH and VL leading to enhanced affinity.